The Effectiveness of Using the Digital Population Identity (IKD) Application in Population Administration Services at the Cirebon Regency Office of Population and Civil Registration - Ernika Nainggolan; Moh.Taufik Hidayat (Journal Of Social Science (JoSS), 2026)
The implementation of e-government has encouraged government institutions to adopt digital innovations in order to improve the quality of public services, including population administration services. One of these innovations is the Digital Population Identity (IKD) application, which is intended to facilitate citizens in accessing identity-based administrative services more efficiently, practically, and securely.. This study aims to examine the level of public awareness and digital literacy regarding the use of the Digital Population Identity (IKD) application, assess public interest and trust in the use of this application compared to physical documents, and examine the extent to which service officials provide adequate guidance during the activation and use of the IKD application. This research employed a qualitative descriptive method. Data were collected through observation, interviews, documentation, and literature review at the Cirebon Regency Office of Population and Civil Registration. The findings show that the IKD application has generally been implemented effectively and has supported the improvement of population administration services. However, its implementation has not yet been fully optimized due to several obstacles, such as limited digital literacy, low public trust in digital identity, inadequate outreach, limited human resources, and the fact that not all institutions have fully recognized digital identity as a substitute for physical documents. Therefore, stronger socialization, improved service assistance, and broader institutional support are necessary to optimize the implementation of IKD and strengthen digital population administration services